2017
DOI: 10.18632/oncotarget.22948
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 regulates macrophage polarization by suppressing MCP-1 expression via miR-124 upregulation

Abstract: Intercellular adhesion molecule-1 is the adhesion molecule mediating leukocyte firm adhesion to endothelial cells, plays a critical role in subsequent leukocyte transmigration. ICAM-1 is also expressed in other cells including macrophages; however, the role of this adhesion molecule in mediating macrophage functions remains enigmatic. We report that ICAM-1 regulates macrophage polarization by positively modulating miR-124 expression. We found higher expression levels of monocyte chemotactic protein-1 in lungs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…111,112 Furthermore, ICAM-1 was found to directly impact macrophage polarization and promote the pro-repair phenotype by positively modulating miR-124 expression. 113 Thus, by enhancing macrophage efferocytosis and the pro-repair reprograming, ICAM-1 can contribute to inflammatory resolution and tissue healing. ICAM-1 expressed by T cells was found to function as a co-stimulatory molecule to promote T-cell activation, 50 where activated regulatory T cells promote the pro-repair function of macrophage by increasing efferocytosis and production of IL-10.…”
Section: Icam-1 and Immune Cell Effector Function In Resolution Of Inmentioning
confidence: 99%
“…111,112 Furthermore, ICAM-1 was found to directly impact macrophage polarization and promote the pro-repair phenotype by positively modulating miR-124 expression. 113 Thus, by enhancing macrophage efferocytosis and the pro-repair reprograming, ICAM-1 can contribute to inflammatory resolution and tissue healing. ICAM-1 expressed by T cells was found to function as a co-stimulatory molecule to promote T-cell activation, 50 where activated regulatory T cells promote the pro-repair function of macrophage by increasing efferocytosis and production of IL-10.…”
Section: Icam-1 and Immune Cell Effector Function In Resolution Of Inmentioning
confidence: 99%
“…Similarly, downregulation of CCL2 expression via overexpression of miR124 in RAW264.7 cells and porcine alveolar macrophages led to decreased M1 and enhanced M2 polarization without any additional stimulation, as measured by expression of M1 (iNOS, IL-6) and M2 (IL-10, MRC1, Ym1) markers. In RAW264.7 cells transfected with miR124 in the presence of LPS, the M1 phenotype could be rescued (95). Apart from Sodhi and Biswas, who confirmed that their CCL2 was endotoxin-free and showed that the effect of CCL2 stimulation could be blocked with an anti-CCR2 antibody (113), other studies cited here leave open the possibility that effects observed may be due to contaminating inflammatory stimuli such as LPS or harder to detect lipoproteins in recombinant protein preparations, or to other cellular changes caused by miR124 overexpression, and require confirmation that the effect was specific to CCL2.…”
Section: Ccl2 Induces Context-specific Macrophage Polarization and Cymentioning
confidence: 99%
“…Moreover, in the murine A-ZIP-Tg CCL2 knockout model, CCL2 deficiency led to reduced ERK1/2 and p38 MAPK phosphorylation (97). In a different study, Gu et al found that silencing the adhesion molecule ICAM-1, which positively modulates expression of the CCL2 mRNA binding miR124, increases CCL2 expression (95). As such, there is still a lot to uncover regarding the underlying signaling mechanisms.…”
Section: Ccl2 Induces Context-specific Macrophage Polarization and Cymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the role of ICAM-1 in macrophages, this also remains controversial. ICAM-1 deficiency increases M2 macrophage polarization and suppress tumor metastasis [65], but others reported that downregulation of ICAM-1 in RAW264.7 macrophages resulted in inflammatory M1 polarization [66]. Therefore, the possible implication of ICAM-1 expression in macrophages and its regulation by butyrate in periodontal tissue homeostasis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%